Improving the Quality of English Learning for Gen Z Through Digital Technology in the Golden Indonesia Era 2045 - Andina Mulia Nanda; Azima Azima; Jeni Agustin; Mikkial Muna; Noralita Putri (Continuous Education: Journal of Science and Research, 2026)
In the era of globalization, English proficiency has become an essential skill, especially for Generation Z, who grow up in technology-rich environments. However, English learning in Indonesia still faces challenges, including moderate proficiency levels and the continued use of traditional, teacher-centered methods. These approaches are often not aligned with Generation Z’s preference for interactive and technology-based learning. This study aims to analyze strategies to improve the quality of English learning for Generation Z through the integration of digital technology in support of the Golden Indonesia 2045 vision. The research applies a qualitative method using a literature review approach. Data were collected from scholarly journals, books, and academic publications related to digital technology and English learning, and analyzed descriptively. The findings show that digital technology enhances learning quality by increasing accessibility, engagement, and effectiveness. Tools such as digital platforms, artificial intelligence, and interactive media support more innovative and student-centered learning environments. Digital literacy also plays a crucial role, as students need the ability to critically access and use information. In addition, the effectiveness of technology integration depends on the balance between technological tools, user competence, and institutional support. In conclusion, digital technology is essential in transforming English learning into a more adaptive and effective process. A comprehensive approach that combines technology, digital literacy, and educational support is needed to prepare Generation Z for global challenges.